SNP variation landscape of BMP15 gene from 75 global sheep breeds and their genetic effect on lambing traits - Liu, Peiyao; Cao, Chunna; Wang, Xiangding; Li, Kewei; Areb, Ebadu; Li, Ran; Zhang, Qingfeng; Pan, Chuanying; Lan, Xianyong (Frontiers in Veterinary Science, 2025)
IntroductionBone morphogenetic protein 15 (BMP15) is a pivotal regulator of reproductive performance. This study aimed to investigate genetic variations in the sheep BMP15 gene and their role in lambing traits.MethodsWhole-genome sequencing was performed on 2,409 individuals from 75 global sheep breeds to identify functional variations in BMP15. Variant annotation, protein structure prediction, haplotype analysis, and association studies with lambing traits were conducted.Results139 SNPs were detected, including 10 exonic variants (6 missense, 2 synonymous, 2 premature stop codons), 9 of which were novel. The high-frequency missense mutation g.54284258A>G (L251P) showed predicted localized conformational changes. Low-frequency stop-gain mutations (e.g., g.54284551C>T) were rare (<0.005%) in domestic breeds. Haplotype H6 (AAAA) predominated in domestic breeds (48.4%), diverging significantly from the wild ancestral H1 (AAGA), indicating artificial selection. The g.54284258A>G variant was significantly associated with live lamb number at first (p < 0.01) and second parity (p  < 0.05). AG genotypes had more live lambs than AA (1.29 vs. 1.12; p < 0.01). No significant associations were found with total lambing number, lamb survival rate, stillbirth count, or stillbirth rate.DiscussionBMP15 exhibits substantial genetic variability shaped by selection. The g.54284258A>G variant significantly influences live lamb numbers and may serve as a genetic marker for improving this trait in sheep breeding programs, though its impact is parity-specific and unrelated to stillbirth or overall survival metrics.